DEVELOPMENT OF PHRASEOLOGICAL UNITS SEMANTICS WITH THE HELP OF OTHER PHRASES. - Jabbarova, Anora (Журнал иностранных языков и лингвистики, 2021)
This article is about development of phraseological units semantics with the help of other phrases. It analyzes the use of phraseological units or its components in an unusual context to create double actualization.